Public Trust Building through Electronic Governance: An Analysis on Electronic Services in Bangladesh - Doullah, Siraj Ud; Uddin, Nasir (Technium Social Sciences Journal, 2020)
Globally, public trust in their government has gradually been declining. It is acknowledged that public trust is the sine qua non of good governance. With the advent of the internet, the influence of ICT on society and the dependence of government on ICTs have grown far beyond our expectations. Moreover, electronic governance and trust foster each others: electronic governance promotes trust, and vice-versa. Other ways, the promotion of electronic government can be a way to increase the citizen trust in government and improve citizen evaluations of government. Simultaneously, many government institutions in both developed and developing countries have entered the digital highway and introduced e-service delivery to the citizens. However, there exists a question of trust in e-governance across the globe as the question of the trust in governance is yet to be solved. This paper intends to illustrate the impacts of online services and initiatives that play imperative role in building public trust in government. It is obvious that there is a significant relationship between public trust and use of ICT based service delivery. The study shows that e-government initiatives can enhance public trust by improving interactions and responsiveness and encouraging participatory mechanisms. Therefore, the government of Bangladesh introduced numerous apparatus/avenues of e-services ranging from education and public utilities to law enforcement. Despite positive impacts, building trust in e-governance has also created special challenges within shifting governance contexts.